The co-evolution of EMNEs and market actors’ institutional works in emerging economies: The case of Korean music agencies in Vietnam - Nguyen, Arthur (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
Research on the coevolutionary approach of Emerging Economy Multinationals (EMNEs) in emerging economies often silences the evolution of EMNEs’ symbolic capacities during their institutional works to shape local markets. Our research fills this gap by investigating how the institutional works of Korean music agencies (KMAs) co-evolve with the institutional works of the Vietnamese market actors in shaping the K-pop music category. Through a longitudinal single case study filled with archival data and interviews, we identify cultural bricolage and cultural engineering as two dimensions of symbolic capacities the KMAs develop during their institutional works. The more specialized the K-pop music category, the more the KMAs’ symbolic capacities evolve from cultural bricolage to cultural engineering.